Etika sebagai Landasan Moral Pembangunan Ekonomi di Indonesia - Suroso Imam Zadjuli (Universitas Islam Indonesia, 2004)
The development of economy constitutes the efforts of economists in every field of trading activities. The goal of those activities is to increase the values of life in keeping the existences and the life needs. To develop economy of nation not only to enlarge the real added values but also to build the character building of society toward more better. In developing economy needs business ethics as moral-base that implies to brother hood and not free fight competition. In this sense, the religious ethics can be consider to become ethics and moral-base of economy activities.